Utility of dynamic ultrasound in the assessment of patellar instability (158). Issue 10 (31st October 2021) - Bhimani, Rohan; Ashkani, Soheil; Mirochnik, Karina; Lubberts, Bart; DiGiovanni, Christopher; Tanaka, Miho
Objectives: Few imaging modalities currently exist that allow for dynamic assessment of the patellofemoral joint. Dynamic evaluation of patellar instability is typically based on physical examination using the Glide test to assess and quantify lateral patellar translation. However, this method can be limited for inexperienced examiners, and precise quantification with this method remains difficult. Therefore, this study aimed to utilize ultrasound imaging to quantify patellar position and translation under dynamic loading conditions to compare knees with and without injury to the medial soft tissue restraints. Methods: 10 fresh frozen, unpaired cadaveric knee specimens underwent assessment of lateral patellar translation using a portable ultrasound device. The probe was positioned 1cm above the medial joint line, and measurements were performed based on the distance between the articular edge of the medial patellar facet and the most prominent edge of the medial trochlear facet. Using an electronic force gauge, two standardized loading conditions were created: (1) Unloaded (0N of force), and (2) loaded with 20N of laterally directed force on the patella to mimic the Glide test. Patellar translation in the lateral direction was assessed from 0-40 degrees of knee flexion at 10 degree increments using a hand held goniometer. Measurements were performed in intact knees and were repeated after arthroscopic transection of the medial soft tissue restraints (both medial patellofemoral ligament [MPFL] and medial quadriceps tendon-femoral ligament [MQTFL]). All measurements were performed using Image J. Paired t-test was used to compare the findings of the intact vs injured states. Sensitivity, specificity, accuracy, negative, and positive predictive value for the injury state were determined based on the values from the intact state +2 standard deviations (SD). P-value <0.05 was considered statistically significant. Results: Compared with the intact state, significant increases in lateralized patellar position and translation were observed when the MPFL and MQTFL were transected, at all flexion angles between 0 and 40 degrees ( p values ranging from .005 to <.001). Results are listed in Table 1. The greatest difference was noted with a laterally directed force of 20N at 20 degrees knee flexion, where a 32.8% (6mm) increase in lateral translation was observed in the injured state, when compared to the intact state. Based on 2 SD from normal values at 20 and 30 degrees, the optimal cutoff point to identify MPFL/MQTFL injury was 17.5 mm of distance from the medial trochlea to the medial patellar facet (sensitivity 95.1%; specificity 86.7%; accuracy 90%). Conclusions: Under dynamic ultrasonographic assessment, the integrity of the medial patellar restraints can be effectively evaluated based on measurements of patellar position and translation, with patellar position >17.5mm from the medial trochlea at 20 and 30 degrees knee flexion indicating the presence of injury. As dynamic ultrasound can be performed without radiation or invasive testing in multiple clinical settings, further studies are recommended to assess the utility of ultrasound based assessments in the evaluation and management of patellar instability.